Environmental Scanning Approach to Assess Innovation and Technology Transfer Performance of Construction Companies - Demirdomen, Gokhan; Isik, Zeynep (UNIV OSIJEK, TECH FAC, 2019)
In construction industry, environmental scanning approach is crucial for companies in strategy development since it informs of the potentials and the barriers of which occurrence is out of control due to its dynamic nature. Nowadays, innovation and technology transfer strategies of construction companies are governed by the changing environmental facts and competitiveness caused by the innovation based demands. This study investigates the effects of environmental factors on the innovation and technology transfer performance of companies by categorizing the factors as either business or general. For this purpose, Structural Equation Modelling (SEM) was used as the analysis method that would enable companies to see those effects were developed. The analysis of the results indicated that general environmental factors and business environmental factors had sequential effects on innovation and technology transfer performance of construction companies highlighting new entrepreneurs in the market and macroeconomic fluctuations.
Keywords: construction industry; innovation and technology transfer; performance assessment; Structural Equation Modelling (SEM); MANAGEMENT; Engineering